Training Positive Rumination in Expressive Writing to Enhance Psychological Adjustment and Working Memory Updating for Maladaptive Ruminators - Yang, Hongfei; Li, Huizhong (Frontiers in Psychology, 2020)
Rumination is associated with psychological adjustment and WM capacity. Studies have shown that psychological interventions such as expressive writing can reduce negative rumination and improve WM capacity. The present study investigated the effect of positive rumination training in expressive writing on psychological adjustment and WM updating. Within an experimental design, positive rumination was manipulated for 10 participants who were maladaptive ruminators in an experiment using a five week training compared to the control group with 9 participants. Results revealed significant enhancement of psychological adjustment and the response time (RT) of WM updating in the experimental group but not in the control group. The two groups did show signifcant difference of all the outcomes in pretest. But the experimental group showed significantly better oucomes than the control group in posttest. The results indicate that positive rumination training in expressive writing is effective and rumination has a causal influence on WM updating capacity.